Effects of Financial Management on Learners’ Performance in Muslim Government Aided Primary Schools in Luwero District, Uganda - Abasi, Lubwama Hamiis; Madinah, Nabukeera; Musa, Matovu (Journal of Education and Practice, 2024)
Purpose: This study aimed at investigating the effect of financial management in Muslim Government aided primary schools on learners’ performance in Luweero District. There so many religious founded Primary schools in the target area but Muslim founded are performing poorly in academics, despite government provides teachers, scholastic materials, supervision and funds equally. Methodology: A casual comparative study design was used following a purposive and simple random sampling method of 371 respondents out of 10,787 populations. Questionnaires were used to collect quantitative data; Interviews were conducted on the selected group of people. Quantitative data was analyzed using descriptive statistics and inferential analysis (correlation) with the aid of SPSS while qualitative data was analyzed using manual thematic analysis. Findings: The study revealed that budgeting has a strong positive and significant effect on learners’ performance (β=0.806, P-value=0.000) at a 0.05 level of significance and further revealed that book keeping has a weak positive and significant effect on learners’ performance in Muslim founded schools in Luweero district (β=0.394, P-value=0.000) at a 0.05 level of significance. Unique contribution to theory, policy and practice: The study recommended that the school management should; embrace the various budgeting techniques to ensure improvement of learner’s performance and achieve financial sustainability. Employ qualified accountants to perform book keeping tasks to aid management decision making in Government aided primary schools in Luweero District